- Thread starter
- #1

#### EqualElement

##### New member

- May 8, 2020

- 4

I'm currently confuse in this one help will be very much needed

- Thread starter EqualElement
- Start date

- Thread starter
- #1

- May 8, 2020

- 4

I'm currently confuse in this one help will be very much needed

- Thread starter
- #3

- May 8, 2020

- 4

I understand the question but don't really know how to prove it.How are you confused?

- Thread starter
- #5

- May 8, 2020

- 4

okay m=1 , n=2 would make it true.

- Thread starter
- #7

- May 8, 2020

- 4

m=2, n=3

m=3, n =4

m=12, n=69.

m=3, n =4

m=12, n=69.

- Mar 31, 2013

- 1,279

= $\frac{n(m+1) - m(n+1)}{m(n+1)}$

= $\frac{n - m}{m(n+1)}$

as n > m >0 so both numerator and denominator positive and hence

$\frac{m+1}{n+1}- \frac{m}{n}> 0$

or $\frac{m+1}{n+1}> \frac{m}{n}$

- Jan 29, 2012

- 1,151

- Jan 30, 2018

- 368

n(m+1)> m(n+ 1). Dividing both sides by the positive number n and n+ 1, $\frac{m+1}{n+1}> \frac{m}{n}$.

It is often useful to see how to prove something by working backward, from the conclusion to the hypothesis. As long as every step is "reversible", it isn't necessary to actually show the reverse. That is called "synthetic proof".